Institutional Relations and religious celebrations in Asturias (Journal of the Sociology and Theory of Religion, 2020)
With the advent of the Social and Democratic State of Law and the implementation of a new Territorial Administration system, implemented in our State, a new territorial distribution with a political-administrative system that decentralized power, adjudicating or giving state powers to territorial entities. In this sense, and due to the attribution of the Magna Carta itself, local authorities acquire some autonomy for the political and administrative exercise of their duties, unknown by the Administration until the moment of the establishment of the Rule of Law. Derived from the decentralization of power and the transfer of powers to Autonomies and local authorities, including island territories, institutional relations, they are or are the prelude to the daily, ordinary or extraordinary legal and competitive acts, which, more or less solemnly, which, At your service, you translate the normative machinery of power attribution. Due to historical roots and social and cultural roots, apart from state non-denominationality, the presence of the Church and other religious confessions in official and unofficial acts is a transcendent and substantial ingredient of the event.Using the case study, during the visit of Her Majesties The Kings, together with the Princess of Asturias and the Infanta, to the Royal site of Covadonga, coinciding with the Official Acts of the day of the Autonomous Community of the Principality of Asturias, and on the occasion of the celebration of the thousand three hundred years of the Kingdom of Asturias in the centenary of the Coronation of the Virgin of Covadonga and the first century of the Covadonga Mountain Park, we will conclude and speak about the importance and heritage of the power / State / Institution relationship, with the Church as an Institution, using the protocol machinery as a link, and element of conjugation, at the service of communication and public relations.
Keywords: Institutional relations, ceremonial, tradition, protocol, festivity, aconfesionality.